Inter-area oscillation damping with non-synchronised wide-area power system stabiliser - Patel A.; Ghosh S.; Folly K.A. (My University, 2025)
One of the major issues in an interconnected power system is the low damping of inter-area oscillations which significantly reduces the power transfer capability. A speed deviation-based wide-area power system stabiliser (WAPSS) is known to be effective in damping inter-area modes which use feedback from remote locations. However, the involvement of wide-area signals gives rise to the problem of time delay, which may degrade the system performance. The delay in synchronised and non-synchronised feedback to WAPSS can have alternate performances. The effect of delays in such WAPSS with two types of feedback is studied and controllers are synthesised using the H∞ control with regional pole placement to ensure adequate dynamic performance. To show the effectiveness of the proposed approach, two power system models have been used for the simulations. It is shown that the controllers designed based on the non-synchronised signals are more robust to time-delay variations than the controllers using the synchronised signal. © The Institution of Engineering and Technology 2018.